Exochorion in the tribe Nymphalini (Lepidoptera: Nymphalidae): the genus Hypanartia Hübner, [1821] and comparison with related genera - Llorente-Bousquets, Jorge; Nieves-Uribe, Sandra; Flores-Gallardo, Adrián (Zootaxa, 2023)
We describe and compare the exochorion of six species of Hypanartia (H. paullus, H. bella, H. lethe, H. godmanii, H. dione disjuncta, and H. trimaculata autumna) using specimens collected in the field and deposited in entomological collections. We used a standard staining technique and scanning electron microscopy to visualize and describe the main exochorionic characters, especially the ridges and the differentiation in the micropylar, perimicropylar, and transition zones in the apical region. We included plates with photographs, drawings, and schemes for clearer visualization of these structures, which are tabulated for comparison. For our characterization, we considered the ridges in colonnade as the main exochorionic feature in the Nymphalini. Thus, we made brief comparisons of these features among several species of the tribe, particularly with the genus Antanartia. The exochorionic characters agree with the separation of groups (paullus group and dione group). By examining the characteristics of H. paullus, the basal species of the paullus group, we found that ridges with conspicuous columns (e.g., in one section only) appears to be the plesiomorphic state, while those with elongated shafts and walls only in the intercolumn represent the apomorphic state.